Implications of minimum tillage and integrated nutrient management on yield and soil health of rice-lentil cropping system – being a resource conservation technology - Bhattacharya, Urjashi; Naskar, Manish Kumar; Venugopalan, Visha Kumari; Sarkar, Smritikana; Bandopadhyay, Pintoo; Maitra, Sagar; Gaber, Ahmed; Alsuhaibani, Amnah Mohammed; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
Conventional tillage methods and indiscriminate use of chemical fertilizers are causes of edaphic problems like soil degradation and loss of soil fertility which reduces crop yield. Puddling now-a-days, has become a major challenge for farmers due to breaking the soil structure, deficit water regimes, and depletion of soil health. Keeping in view, the absolute need to fulfill food security as well as sustainability, an experiment was conducted for 2 years on a rice-lentil cropping system during 2018–2019 and 2019–2020 in sandy clay loam soil of a new alluvial zone of eastern India to evaluate effects of minimum tillage and integrated nutrient management on yield and soil health. Conventional tillage (CT) direct seeded rice-lentil, Minimum tillage(MT) direct seeded rice-lentil, MT transplanted rice-lentil and MT direct seeded rice-lentil were kept as main plot treatments and control (without any fertilizer), 100% RDF, 75% nitrogen + FYM, 75% nitrogen + FYM + Azospirillum and 75% Nitrogen + FYM + Azospirillum sp. + Zinc Sulphate were kept as subplot treatments during the study. Though conventional tillage treatments recorded higher LAI, CGR and yield in the first year of study in the case of rice; during the second year, minimum tillage treatments showed significantly (p ≤ 0.05) better results in the aforesaid aspects with MTDSR-L having a maximum yield of 5.17 t ha−1. In the case of lentil minimum tillage treatments had better results for both years, with MTDSR-L treatment having the highest yield of 8.084 t ha−1. Among the nutrient schedules, the crops had better LAI, CGR and yield during the first year in the case of 100% RDF treatment, but in the second year, 75% Nitrogen + FYM + Azospirillum sp. + Zinc Sulphate had the highest respective values. Soil organic carbon was marginally improved by both tillage and nutrient treatments, while soil microbial biomass carbon, dehydrogenase activity and microbial count were significantly influenced. The combination of MTDSR-L and 75% Nitrogen + FYM + Azospirillum sp. + Zinc Sulphate (N5) treatment showed the maximum values for all soil biological parameters leading to improve soil health. The results of the experiment concluded that the practice of minimum tillage and integrated nutrient management may be recommended to enhance the yield and stability of rice-lentil cropping systems in sandy clay loam soil of a new alluvial zone of eastern India by acting as an alternative for the decline of soil health.